2005
DOI: 10.1128/jvi.79.18.11588-11597.2005
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Simplex Virus Glycoprotein B Binds to Cell Surfaces Independently of Heparan Sulfate and Blocks Virus Entry

Abstract: Herpes simplex virus (HSV) is responsible for mucocutaneous lesions, commonly known as cold sores, and genital lesions or herpes genitalis. After primary infection virus resides latent in sensory and autonomic neurons from where it reactivates periodically (66). Among the important steps in infection, attachment and entry have attracted attention as targets for therapeutic treatments and vaccines. Binding and entry are complex biochemical processes involving 5 of the 12 known surface glycoproteins of the virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
116
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(122 citation statements)
references
References 68 publications
5
116
1
Order By: Relevance
“…The gB homologues of HCMV and other herpesviruses contribute to virion attachment onto cells through interactions with heparan sulfate GAGs and may interact with more specific, saturable receptors (32,33). However, in contrast to gH/gL/ UL128-131, gB expression in ARPE-19 cells did not interfere with HCMV infection (Fig.…”
Section: Expression Of the Hcmv Gh/gl/ul128 -131 Complex Renders Epitmentioning
confidence: 89%
“…The gB homologues of HCMV and other herpesviruses contribute to virion attachment onto cells through interactions with heparan sulfate GAGs and may interact with more specific, saturable receptors (32,33). However, in contrast to gH/gL/ UL128-131, gB expression in ARPE-19 cells did not interfere with HCMV infection (Fig.…”
Section: Expression Of the Hcmv Gh/gl/ul128 -131 Complex Renders Epitmentioning
confidence: 89%
“…29,30) Binding of HSV to host cells and entry of HSV into host cells are mediated by a complex process involving the essential viral glycoproteins B (gB), gD, gH, and gL and multiple celluar receptor molecules, including the tumor necrosis factor receptor family members nectin-1 and nectin-2, herpesvirus entry mediator, heparan sulfate proteoglycans, and two members of it the mmunoglobulin superfamily. [43][44][45] HSV entry is inhibited by cholesterol-sequestering drugs such as methyl-b-cyclodextrin and nystatin. Moreover, HSV gB has been detected in lipid rafts after virus attachment and during entry.…”
Section: Role Of Lipid Rafts In Virus Entrymentioning
confidence: 99%
“…Third, large antigens as well as immunomodulatory molecules can be delivered to DCs concurrently by a single HSV amplicon, because of its inherently high transgene capacity, providing higher flexibility in regulating immune responses (Bowers et al, 2003). Herpes simplex virus (HSV) gains its entry into cells by fusion of viral envelope with the cell surface membrane though a cascade of interactions involving multiple viral glycoproteins and cellular receptors (Bender et al, 2005;Kwon et al, 2006;Spear et al, 2006). It has been demonstrated that DCs interact with HSV in a glycoprotein-dependent and Tolllike receptor-2 (TLR2)-independent manner (Reske et al, 2008).…”
Section: Discussionmentioning
confidence: 99%